KAJIAN KETAHANAN PANGAN RUMAH TANGGA PETANI MENDONG DAN PETANI PADI - Suyudi Suyudi; Hendar Nuryaman; M Iskandar Mamoen; Tenten Tedjaningsih (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Food security for farm households is strongly influenced by food and non-food production from their farming products. Income farming will not be the same if the land cultivated by farmers is different between mendong farming and rice. This study aims to describe the proportion of food expenditure of mendong and paddy farmers in relation to the proportion of food and non-food expenditure, and analyze the degree of food security of the two households. The research method uses survey techniques, with census sampling of 18 households of mendong farmers and 15 rice farmers in Manonjaya District, Tasikmalaya Regency. Data analysis was carried out descriptively and analysis of the share of Food Expenditures Equation, Energy Consumption Rate and quadrant analysis. The results of the study show that household profile of farmers and rice farmers viewed based on the proportion of food and non-food expenditure shows that the food expenditure of the two households is low, because most of it is used for non-food consumption. The degree of household food security based on Food Expenditures Share and Energy Consumption Rate is in the low category both for mendong farmers and rice farmers because those with food security status are <50%, and none are included in the food insecurity category for both households.